Regulatory T cells--a journey from rodents to the clinic. - Long, E; Wood, K (2007)
Over the past decade our understanding about a subset of T lymphocytes, now termed regulatory T cells (Tregs) and previously known as suppressor T cells, has increased immensely. Tregs can induce and maintain immune tolerance and have the capacity to facilitate antigen-specific long-term graft survival successfully in animals receiving allogeneic organ transplants. The development of approaches to generate alloantigen reactive Tregs would provide an exciting and effective adjunct or alternative therapy to the life-long program of immunosuppression currently necessary to prevent graft rejection in the clinical setting. This review will focus on how rodent experimental models have helped us to figure out how Tregs could be induced in humans and harnessed to enable long-term transplant acceptance.